Correlation of HCT-ALB, SmtO2, CRT and Lac with renal impairment and prognosis in patients with septic shock: Correlation of biomarkers with renal impairment in septic shock - Liang, Peipei; Wei, Zhijian; Xia, Junjie; Yu, Feng (Journal of Medical Biochemistry, 2024)
Background: This study investigates the correlation between the difference in hematocrit (HCT) and serum albumin (ALB) levels (HCT-ALB), muscle tissue oxygen saturation (SmtO2), capillary refill time (CRT), and blood lactate (Lac) with the severity of renal function damage and prognosis in patients with septic shock. Methods: Conducted from February 2022 to February 2024, this study included 116 septic shock patients treated at the First Affiliated Hospital of Anhui Medical University. Patients were divided into groups based on whether they developed acute kidney injury: 40 patients were included in the acute kidney injury group, and the remaining 76 were placed in the non-kidney injury group. The levels of HCT-ALB, SmtO2, CRT, and Lac were compared between the groups. Patients were followed up to assess their 28-day survival outcomes; 75 surviving patients were placed in the survival group, and 41 deceased patients in the death group. Differences in clinical data and levels of HCT-ALB, SmtO2, CRT, and Lac between the two groups were analyzed to explore the relationship of these indicators with patient prognosis. Results: Levels of HCT-ALB, CRT, and Lac were higher, while SmtO2 was lower in the acute kidney injury group compared to the non-kidney injury group (P<0.05). Similarly, the death group exhibited higher levels of HCT-ALB, CRT, and Lac and lower SmtO2 levels compared to the survival group (P<0.05). Univariate and multivariate analyses revealed that HCT-ALB, SmtO2, CRT, and Lac significantly impact patient survival outcomes, demonstrating high predictive value for patient mortality with respective AUC values of 0.834, 0.782, 0.903, and 0.918. The combined application of these indicators for predicting patient mortality had an AUC value of 0.985, which is higher than when the indicators were used individually. Conclusion: HCT-ALB, SmtO2, CRT, and Lac are significantly elevated in patients with acute kidney injury and deceased patients, closely correlating with the severity and prognosis of septic shock. These indicators can serve as important biomarkers for assessing the condition and prognosis of these patients.